Kepemimpinan Kyai dalam Usaha Mengembangkan Pendidikan Islam di TPQ As-Sholihi - Qomar, Abd (LP3M Universitas Islam Zainul Hasan Genggong, 2018)
Quran Education Park (TPQ) is a growing phenomenon in the world of social society, as a form of educational park for early childhood. The phenomenon emerged as an alternative solution to kyai leadership in TPQ and as one important factor in achieving the goal to overcome the difficulties of children, especially in learning the Qur'an. This is very urgent because TPQ is an institution of Islamic Education which grows and is recognized by the community. Based on the above thoughts, the authors are interested to conduct research related to the leadership of kyai in an effort to develop Islamic education in TPQ As-sholihi Pajarakan. This study discusses the leadership of kyai in an effort to develop Islamic education in TPQ As-sholihi Pajarakan with the formulation of the problem as follows: 1) How is the Kyai leadership type in TPQ As-sholihi Pajarakan? 2) What efforts did the kyai make in developing Islamic education in TPQ As-sholihi Pajarakan? The purpose of this research is 1) Describe the type of leadership of Kyai in TPQ As-sholihi Pajarakan. 2) Identify kyai's efforts in developing Islamic education in TPQ As-sholihi Pajarakan. From the results of this study shows that TPQ in carrying out its function as a supporting unit of education in the community and in realizing the vision, its mission using the type of leadership kharismatik (authority kyai), authoritarian (punishment on santri) and democratic (cooperation with program supporters), it was seen on existing programs in TPQ. Types of leadership are run because of limited human resources (HR), especially in terms of acceptance of new students and skills improvement. While kyai business in developing Islamic education in TPQ As-sholihi Pajarakan is to maximize the program of increasing the competence of santri as well as improving the quality and quantity of worship. Both programs are directly directed by the TPQ leader as the person in charge who is the interpreter of TPQ's vision and mission. Keywords: kyai, leadership, Islamic education